Effects of large river dam regulation on bacterioplankton community structure. Issue 2 (14th January 2013) - Ruiz‐González, Clara; Proia, Lorenzo; Ferrera, Isabel; Gasol, Josep M.; Sabater, Sergi
Abstract Large rivers are commonly regulated by damming, yet the effects of such disruption on prokaryotic communities have seldom been studied. We describe the effects of the three large reservoirs of the Ebro River (NE Iberian Peninsula) on bacterioplankton assemblages by comparing several sites located before and after the impoundments on three occasions. We monitored the abundances of several bacterial phylotypes identified by rRNA gene probing, and those of two functional groups (picocyanobacteria and aerobic anoxygenic phototrophic bacteria‐AAPs). Much greater numbers of particles colonized by bacteria were found in upstream waters than downstream sites. Picocyanobacteria were found in negligible numbers at most sites, whereas AAPs constituted up to 14% of total prokaryotes, but there was no clear effect of reservoirs on the spatial dynamics of these two groups. Instead, damming caused a pronounced decline in Betaproteobacteria, Gammaproteobacteria and Bacteroidetes from upstream to downstream sites, whereas Alphaproteobacteria and Actinobacteria significantly increased after the reservoirs. Redundancy analysis revealed that conductivity, temperature and dissolved inorganic nitrogen were the environmental predictors that best explained the observed variability in bacterial community composition. Our data show that impoundments exerted significant impacts on bacterial riverine assemblages and call attention to the unforeseen ecological consequences of river regulation.